THE USE OF E-COMMERCE AND SOCIAL MEDIA AS CATALYST TOWARD REVENUE ENCHANCEMENT (CASE STUDY: 92 Coffee): - - Fani, Stefanie; Desma Erica Maryati Manik (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
Along with the times, many people are fond of consuming coffee. Until now, consuming coffee has become a trend among the people and has influenced many enthusiasts to build a business in the coffee sector, one of which is 92 Coffee. The more coffee outlets there are, the tougher the competition will be. Meanwhile, MSME businesses collaborate with other brands or well-known figures in the world of social media (celebgrams), and use marketing/branding services to help introduce and spend the products issued and build brand image. Therefore, 92 Coffee needs to pay attention to the right marketing strategy in order to be able to reach and expand the target market. The purpose of this study is to find out how to expand the target market through social media and e-commerce and what causes an MSME business to grow faster. The research method used is a quantitative survey method. This method is used to conduct questionnaires to respondents who are customers of 92 coffee and business owners. Through this research method, we will be able to find out the weaknesses, opportunities, credibility, and marketing strategies applied by 92 Coffee, which can be known through the results of a customer survey of 92 Coffee.